ENHANCING THE TENTH GRADERS’ READING COMPREHENSION ACHIEVEMENT THROUGH K-W-L STRATEGY WITH TWIN-TEXTS AT SENIOR HIGH SCHOOL IN PALEMBANG - PERDANA, JOSI EKA PANTARA; MIRIZON, SONI; ZURAIDA, ZURAIDA
The objectives of this study are to find out: (1) whether or not there is any significant difference in students’ reading comprehension achievement after they are taught through K-W-L strategy with twin-texts and (2) whether or not there is any significant difference in students’ reading comprehension achievement between the students who are taught through K-W-L strategy with twin-texts and those who are not. The sample of this research was 64 tenth graders of one high school in Palembang, which were divided into control group and experimental group; each group consisted of 32 students. The technique of selecting the sample was purposive sampling. The data were obtained through reading comprehension test and were analyzed by using paired sample t-test and independent sample t-test. The result of this study showed that (1) the mean difference in posttest and pretest of experimental group was 12.29 and p value <0.05. It means that there was a significant difference in reading comprehension achievement after the students were taught through K-W-L strategy with twin-texts, (2) the mean difference between posttest of both experimental group and control group was 11.688 and p value <0.05. It means that there was a significant difference in reading comprehension achievement between the students who were taught through K-W-L with twin-texts and those who were not. In conclusion, teaching reading comprehension through K-W-L strategy with twin-texts was effective to enhance students’ reading comprehension achievement.